Uji Kesukaan Kue Lumpur Dengan Substitusi Tepung Kelapa - Melati Fauziana; Priyanto (Eduturisma, 2025)
The background of this research was carried out because coconut meat has good nutritional content as a source of food nutrition which is important for providing health benefits and providing new innovations from kue lumpur. Kue lumpur is a typical Indonesian snack originating from Sidoarjo, East Java. Kue lumpur is made from the main ingredients, potatoes, flour, sugar, coconut milk and egg to produce the characteristic of a kue lumpur that is smooth and soft. The purpose of this study was to obtain the best ratio of coconut flour substitution to the characteristics of kue lumpur and to find out the level of public liking and acceptance of kue lumpur. This research uses literature study, questionnaire and observation. The results of the research that has been done have the characteristics obtained from kue lumpur with a 20% substitution of coconut flour with aroma scores (3.6), color (3.8), taste (3.86), texture (3.78) and an overall score of 15.04, because it doesn’t use too much coconut flour which has quite coarse particles, so it doesn’t change to much in terms of aroma, color, taste and texture of the kue lumpur.